Polyphenols’ Impact on Selected Biomarkers of Brain Aging in Healthy Middle-Aged and Elderly Subjects: A Review of Clinical Trials - Ziegler, Tobias; Tsiountsioura, Melina; Meixner-Goetz, Lisa; Cvirn, Gerhard; Lamprecht, Manfred (Nutrients, 2023)
With a constantly growing elderly population, incidences of neurodegenerative diseases are also rising and are expected to further increase over the next years, while costing health systems across the world trillions of dollars. Therefore, biomarkers to detect manifestations of brain aging early and interventions to slow down its pace are of great interest. In the last years, the importance of the neurotrophins brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in the context of cognitive function and the aging brain has increased, besides the already well-established amyloid-beta (Aβ) and tau plaques. Due to their wide range of beneficial health effects as well as their antioxidant and anti-inflammatory properties, a class of secondary plant-metabolites, the so-called polyphenols, gained increasing attention. In this review, we discuss the roles of BDNF, Aβ, NGF, and tau proteins as biomarkers of brain aging and the effect of dietary polyphenol interventions on these biomarkers, assessed via blood analysis, magnetic resonance imaging (MRI), and positron emission tomography (PET).